2020
DOI: 10.20469/ijbas.6.10002-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Trust Towards Content Marketing of Food & Beverage Businesses on Instagram: Empirical Analysis of Taiwanese and Singaporean Consumers

Abstract: Nowadays, food and beverage businesses need some adjustments regarding their marketing strategy as people's lifestyle, and dietary patterns are varied. One of the marketing strategies on social media which local restaurant marketers can adopt is content marketing. However, content marketing will not work until trust is established (Newman, 2014). Marketers must ensure that the contents are genuine and transparent enough to develop trust (Kee & Yazdanifard, 2015). This study aims to examine the effect of produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Based on the fourth hypothesis testing results, it can be inferred that advertising content value had a positive and significant direct effect on brand trust. The results of this study confirm the previous research by Lou and Yuan [5] and Mohammad [26]. The content that is considered to explain best the role of advertising content value shared by influencers is fun content, content that helps understand the product better, and content that followers can enjoy.…”
Section: Evidence For Structural Fitsupporting
confidence: 88%
“…Based on the fourth hypothesis testing results, it can be inferred that advertising content value had a positive and significant direct effect on brand trust. The results of this study confirm the previous research by Lou and Yuan [5] and Mohammad [26]. The content that is considered to explain best the role of advertising content value shared by influencers is fun content, content that helps understand the product better, and content that followers can enjoy.…”
Section: Evidence For Structural Fitsupporting
confidence: 88%
“…When the digital brand content is clear, presented appealingly, and focuses on user value while consumers can opt out any time, brand trust is enhanced (Hollebeek & Macky, 2019). On the other hand, Mohammad (2020) found that brand trust is enhanced with digital brand content that promotes product transparency.…”
Section: Discussionmentioning
confidence: 99%